A proposal of Heynsnema gen. n. (Dorylaimida: Tylencholaimidae), a remarkable dorylaim from South Africa (Journal of Nematode Morphology and Systematics, 2012)
The identity of three South African species originally described as belonging to the genusThonus is discussed. These species share a very similar morphological pattern mainly characterized by a unique combination of characters: cuticle dorylaimoid, lip region cap-like, pharyngeal expansion occupying about three-fi fths of total neck length, female genital system amphidelphic, pars refringens vaginae lacking or very reduced, tail rounded conoid and similar in both sexes, and 7-10 contiguous ventromedian supplements. Heynsnema gen. n. is erected to accommodate them. The new taxon resembles several qudsianematid and tylencholaimid genera, its relationships with them being analysed in detail; it is tentatively or provisionally classifi ed under the family Tylencholaimidae. New data of the three species are provided, including additional observations on their morphology, morphometrics and illustrations.